1979
DOI: 10.1128/aac.16.4.468
|View full text |Cite
|
Sign up to set email alerts
|

Urinary casts as an indicator of renal tubular damage in patients receiving aminoglycosides

Abstract: We assessed the value of quantitative cast excretion as an early marker of renal tubular damage in 154 seriously ill patients. One hundred twenty-four of these received aminoglycoside antibiotics, and 30 of the 124 experienced a rise in serum creatinine of 0.5 mg/dl or more during therapy. The remaining 30 of the 154 patients were treated with other antibiotics and served as controls. Casts were quantitated in random urines collected before morning diuretic doses. Cast counts in control patients averaged 44 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…Previous studies showed that the identification of granular casts and RTEC in the urine sediment analysis correlates well with ATN (17,18). Schentag et al (17) demonstrated that the increase in urinary cast excretion provides information about kidney injury that allows one to adjust aminoglycoside dosages 5 to 9 d before a rise in serum creatinine concentration develops in patients with aminoglycoside nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the identification of granular casts and RTEC in the urine sediment analysis correlates well with ATN (17,18). Schentag et al (17) demonstrated that the increase in urinary cast excretion provides information about kidney injury that allows one to adjust aminoglycoside dosages 5 to 9 d before a rise in serum creatinine concentration develops in patients with aminoglycoside nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Serum creatinine levels and 24-h creatinine clearance values were determined by autoanalyzer methods; 24-h urinary excretion of 82-microglobulin was determined by the radioimmunoassay, and values of more than 50 mg/24 h were associated with nephrotoxicity (4). Quantitative cast counts were performed daily on random urine samples, and values of more than 500 casts per mil on 3 consecutive days were associated with nephrotoxicity (10 on April 27, 2019 by guest http://aac.asm.org/ Downloaded from increase in the creatinine level. These abnormal values were more than 200 mg for gentamicin and more than 175 mg for tobramycin (15).…”
Section: Methodsmentioning
confidence: 99%
“…Rates of aminoglycoside administration were determined individually for all patients according to nomograms and measured peak and trough serum concentrations. Blood for assays was obtained throughout treatment and in most patients for 10 to 20 days after aminoglycoside treatment was stopped (to quantitate the terminal halflife), as previously described (9,10,(11)(12)(13)15 Assays. Serum, urine, and postmortem tissue aminoglycoside concentrations were measured by both a microbiological assay and a radioimmunoassay, as previously described (12,13).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative cast counts were performed daily on random urines collect-ed in the morning. Values exceeding 500 casts per ml for 3 days were defined as nephrotoxic damage (14).…”
Section: Methodsmentioning
confidence: 99%